MANIFESTATION OF COVID-19 IN THE SECOND TRIMESTER OF PREGNANCY: FEATURES OF GESTATION, OBSTETRIC AND PERINATAL OUTCOMES - Людмила Станиславовна Ищенко; Екатерина Евгеньевна Воропаева; Элла Алексеевна Казачкова; Евгений Леонидович Казачков; Татьяна Николаевна Шамаева; Елена Романовна Вейсенборн; Юлия Сергеевна Ищенко (Мать и дитя в Кузбассе)
Information continues to accumulate about the characteristics of the course and outcomes of pregnancy and childbirth during the manifestation of the new coronavirus infection COVID-19. Most studies focus on the third trimester of gestation. Data on the impact of COVID-19 on a pregnant woman and fetus in the second trimester are scarce and contradictory. The aim of the research – to assess the characteristics of the course and outcomes of pregnancy in women with the manifestation of COVID-19 of varying severity in the second trimester of gestation. Materials and methods. 456 pregnant women with manifestations of COVID-19 of varying severity in the second trimester of gestation - the main study group. Patients of the main group, depending on the severity of COVID-19, were divided into 4 groups: with a mild course (n = 137) – group 1, with a moderate course (n = 259) – group 2, with a severe course (n = 50) – 3 group with extremely severe infection (n = 10) – group 4. 90 women in the third trimester of gestation who had no history of COVID-19 during this pregnancy – a comparison group. Results. COVID-19, which manifests itself in pregnant women in the second trimester, is statistically significantly more likely to have a mild and moderate course in the cohort of hospitalized patients (p < 0.001). Against the background of the manifestation of COVID-19 of any severity, there is a statistically significant increase in the frequency of PN compared with uninfected pregnant women (p < 0.001; p1.5 < 0.001; p2.5 < 0.001; p3.5 < 0.001; p4.5 < 0.001). Diabetes mellitus is registered statistically significantly more often in severe and extremely severe cases compared to pregnant women without COVID-19 (p = 0.001; p3.5 = 0.005; p4.5 = 0.002). During the period of manifestation, as the severity of COVID-19 increases, it is accompanied by a statistically significant increase in the frequency of premature birth (p < 0.001; p1.3 = 0.002; p1.4 < 0.001; p2.3 < 0.001; p2.4 < 0.001; p3.4 < 0.001). Induced premature births are registered statistically significantly more often in severe and extremely severe infections (p = 0.001; p1.3 = 0.005; p1.4 = 0.005). In cases of extremely severe COVID-19, cases of maternal death are recorded (2/456 – 0.4 %). Mild and moderate COVID-19 is associated with a statistically significantly higher rate of stillbirth (p = 0.001; p1.3 = 0.005; p2.3 = 0.002). During the period of convalescence after severe COVID-19, a statistically significantly higher incidence of diabetes mellitus that developed during pregnancy is recorded (p < 0.001; p1.3 = 0.001; p2.3 = 0.002; p3.5 < 0.001). Delivery is associated with a statistically significant increase in the rate of cesarean section in convalescents with mild and moderate COVID-19 compared with uninfected pregnant women (p = 0.002; p1.5 = 0.001; p2.5 < 0.001). Regardless of the severity of the infection, there is a statistically significant decrease in the weight of newborns in convalescents compared to pregnant women without COVID-19 (p < 0.001; p1.5 = 0.002; p2.5 < 0.001; p3.5 = 0.002). Conclusion. Against the backdrop of the manifestation of COVID-19 in the second trimester, the likelihood of complications of pregnancy and childbirth and adverse perinatal outcomes increases. The period of convalescence, in general, is associated with the successful completion of gestation for the mother and fetus, regardless of the severity of COVID-19 in the anamnesis.